Hubungan Antara Iklim Sekolah Dengan School Well-Being Pada Siswa Smk X - Erlisa Winda Pertiwi; Rima Wilantika (Psikologi Prima, 2024)
School well-being refers to students' feelings of happiness when their basic needs at school are met, encompassing school conditions, social relationships, self-fulfillment, and school health. One of the factors influencing school well-being is the school climate. This study aims to examine the relationship between school well-being and school climate among 11th-grade students at SMK X Gadingrejo. Using a quantitative approach and purposive sampling technique, the study involved 100 students from the total population of 11th graders. The data analysis used was product-moment correlation with SPSS 25.0, revealing a significant positive relationship (r = 0.406, ρ = 0.000) between school climate and school well-being, with an effective contribution of 16.5%. These findings highlight the importance of fostering a supportive school environment through collaborative activities, improved facilities, and personal development programs to enhance students' well-being.